#DiminishingDiscrimination: The symbolic annihilation of race and racism in news hashtags of 'calling 911 on Black people'. (January 2022) - Gutsche, Robert E; Cong, Xinhe; Pan, Feihong; Sun, Yiyi; DeLoach, LaTasha
This critical textual analysis examines the symbolic annihilation of race and racisms by the use of hashtags, such as #BBQBecky and #CornerstoreCaroline, in news coverage of White people in the United States who called or threatened to call 911 to report everyday behavior of Black individuals in 2018. This study argues that the use of humorous and virtual hashtags to represent the callers contributed to overall coverage of racially charged incidents in ways that reduced the events' seriousness in terms of social policing of Black individuals. Collectively, this coverage formed a type of symbolic annihilation of racist interpretations of callers' acts and Black resistance and meanings embedded within the hashtags themselves.